Retrieval of Terrestrial Plant Fluorescence Based on the In-Filling of Far-Red Fraunhofer Lines Using SCIAMACHY Observations - Khosravi, Narges; Vountas, Marco; Rozanov, Vladimir V.; Bracher, Astrid; Wolanin, Alexandra; Burrows, John P. (Frontiers in Environmental Science, 2015)
Chlorophyll fluorescence is directly linked to the photosynthetic efficiency of plants. As satellite-based remote sensing has been shown to have the potential to derive global information about fluorescence it has become subject of various recently published studies stimulating an upsurge in this research field. This manuscript presents a simple and fast retrieval method for solar induced terrestrial plant fluorescence (SIF) which relies on only a few prerequisites. The spaced based remote sensing spectrometers used in this work typically exhibit an additive spectral feature, which is not fluorescence. This is often accompanying the actual SIF retrieval and can significantly deteriorate the results. To account for this effect a correction method has been developed and is combined with the retrieval. The method has been applied to ten years of SCIAMACHY data with promising results. The retrieved SIF values are lying between 0 and 4 mW [m-²,sr-¹,nm-¹]. However, most of the retrieved values are not exceeding 1.5 [m-²,sr-¹,nm-¹], agreeing with previous studies on the subject. Results have been retrieved for SCIAMACHY spatial resolution of 240 x 30 km² and gridded to 80 arc minutes. A clear seasonal variation could be shown utilizing 10 years of SCIAMACHY data (2002-2012). In absence of large area ground based validation data a final judgment of the results presented is not feasible. However, a direct comparison to data of others was showing similar results for most areas.